Behavior and nest architecture of the bee Caenohalictus alexandrei (Hymenoptera, Halictinae) - Cindy Julieth Celis; Marlene Lucia Aguilar-Benavides; José Ricardo Cure (Papéis Avulsos de Zoologia, 2023)
Abstract In Colombia, few studies have focused on nest architecture, behavior or sociality of wild bees. This study provides basic information on the nests of Caenohalictus alexandrei and presents behavioral observations outside the nests, derived from direct field observation of 40 nests and 39 male sleeping cavities in two localities of the Savanna of Bogota, Colombia. We recognized four different behavioral activities carried out by adult females: foraging, guarding, opening and closing of the entrance of the nest, with foraging being the most frequent of them. The observed activities were carried out more frequently from 9:00 h to 13:00 h. Males were observed performing two behavioral activities in the sleeping cavities: staying at the cavity entrance and cavity departure. A third male activity, corporal grooming, was carried out outside the sleeping cavity. Our field observations indicate that more than one adult female was active simultaneously performing the different tasks within a single nest. The nests presented different levels of complexity in their architecture, depending on the age of the nest and number of adult females in them. Descriptions of the nesting sites and behavioral activities as well as illustrations of the nest architecture are provided.